In Memoriam: David MacDonald (1943-2025), Friend and Mentor - Fox, Mark (KOINON: The International Journal of Classical Numismatic Studies, 2025)
Has the reader ever thought what is the point in having friends? If we don’t die first or simultaneously with them, then they will be first in line. And then we are in pain, which may last the rest of our lives. Is it worth it? Would it not be better to live without becoming too close to one another, to keep our relationships strictly professional? Recently, in a homily I heard, I was made aware of the extreme outcome of this philosophy of insulating ourselves from all pain, all hurt, for there is a place where this approach can be perfected. It is called Hell.